(untitled) (Bangladesh Journal of Medical Science, 2011)
Objective: Developmental disturbances of teeth contribute to dental problems encountered in general practice. These are a group of disorders where prevention is not possible, with the exception of environmental enamel hypoplasia. Surveys done on various populations have found prevalence of dental anomalies to be 5.46%. Knowledge of common dental anomalies when available can be a useful tool for forensic dentistry. Since such epidemiological data is not available for the Jodhpur population in Rajasthan, this study was conducted to determine the prevalence of developmental dental anomalies in 500 school going children. Methodology & Result: A total of 500 school children (290 male & 210 female) of age ranging between 6 - 15 years were examined clinically for developmental anomalies of teeth. Prevalence of Peg lateral, supernumerary teeth & Talon’s cusp was 0.4%, 0.6% & 0.2% respectively while 18.8% showed fluorosis induced enamel hypoplasia. Key Words: Dental anomalies; Peg lateral; supernumerary teeth; Talon’s cusp; Enamel hypoplasia. DOI: 10.3329/bjms.v10i1.7318 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.41-44